2023
DOI: 10.3390/life13030786
|View full text |Cite
|
Sign up to set email alerts
|

Capsaicin Ameliorates the Cyclophosphamide-Induced Cardiotoxicity by Inhibiting Free Radicals Generation, Inflammatory Cytokines, and Apoptotic Pathway in Rats

Abstract: Cyclophosphamide is an antineoplastic agent that has a broad range of therapeutic applications; however, it has numerous side effects, including cardiotoxicity. Furthermore, chili peppers contain a substance called capsaicin, having antioxidant and anti-inflammatory effects. Thus, this research paper focuses on the potential mechanism of capsaicin’s cardioprotective activity against cyclophosphamide-induced cardiotoxicity by measuring the expression of oxidative and inflammatory marker such as interleukins and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…A study conducted in mammalian heart tissue cells reported that excessive production of free oxygen radicals during CP therapy caused lipid peroxidation, and the resulting membrane damage disrupted the integrity of the myocardial membrane and caused dysfunction 10 . In his study, Shanholtz 16 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study conducted in mammalian heart tissue cells reported that excessive production of free oxygen radicals during CP therapy caused lipid peroxidation, and the resulting membrane damage disrupted the integrity of the myocardial membrane and caused dysfunction 10 . In his study, Shanholtz 16 .…”
Section: Discussionmentioning
confidence: 99%
“…On the eighth day, a single dose of CP (200 mg/kg) was administered intraperitoneally. The dosages of CP (Endoxan, 1 g vial containing IV infusion powder, Eczacıbaşı, Baxter Oncology GmbH Halle, Germany) and RA (536954-5 g, 96% Sigma-Aldrich Chemie Gmbh) used in this study were determined according to the literature review 9,10 .…”
Section: Experimental Designmentioning
confidence: 99%
“…The present findings demonstrate that the levels of Bax and caspase-3 increase following Cyclo injection while the level of BcL2 declines; this initiates the apoptotic pathway, which is associated with the presence of oxidative stress and subsequent DNA damage. Ultimately, these events culminate in the activation of the mitochondrial apoptotic pathway through a reduction in the levels of antiapoptotic proteins ( Mahmoud et al, 2017 ; Ahmed et al, 2023 ). It has been demonstrated that 150 mg/kg/day of Cyclo markedly increase the proapoptotic proteins caspase-3 and caspase-9 in the cardiac tissues of Wistar rats ( Adeyemi et al, 2024 ).…”
Section: Discussionmentioning
confidence: 99%
“…The previous literature has extensively reported that the administration of cyclophosphamide and fluorouracil can induce cardiotoxic effects, as indicated by the observed increase in troponin I and CK-MB concentrations [ 56 , 57 , 58 ]. The current study evaluated the concentrations of troponin I, creatine kinase (CK), and creatine kinase-MB (CK-MB) following CMF interventions.…”
Section: Discussionmentioning
confidence: 99%